Analisis Model Pondasi Bangunan Air di Atas Tanah Rawa Berbahan Lokal - Kelik Istanto; Andy Eka Saputra (Jurnal Ilmiah Teknik Pertanian - TekTan, 2013)
The research was distributed by foundation failure that supportted the waterworks on swamp soil which caused it collapsed. The objectives of this research were (1) Define foundation model on swamp soil using local material that suitable to swamp soil characteristic, (2) Generate foundation model that give efficiency value more than or equivalence to 70%, and, (3) Predict the bearing capacity of foundation model to support waterworks load. The proposed foundation models were pile group using gelam (melaleuca cajuputi sub sp.cumingiana) had 12 cm in diameter which plugged upright (M1), two-fifths in each row were plugged oblique with 15o to center line of waterworks (M2), and four-fifths in each row were plugged oblique with 15o to center line of waterworks (M3). Furthermore, it performed by computing the bearing capacity of each foundation model based on physical and mechanical properties of swamp soil in single pile, pile group, and block failure system. The research results shown that 40 cm in space between piles (Eg=70,3%), the foundation models produced the same bearing capacity to support waterworks load. Whereas, which 50 cm in space (Eg=76%), 60 cm (Eg=79,9%), and 70 cm (Eg=82,7%), each model produced different bearing capacity to support waterworks load and could describe by QM1<QM2<QM3. The maximum waterworks load could be supported by foundation model was 1,208.83 kg, it was happened in the third model with 70 cm in space.Â Keywords:Â  swamp soil, local material, pile group efficiency, and bearing capacity